The association of serum uric acid with cognitive impairment and ATN biomarkers - Huang, Shan; Wang, Jun; Fan, Dong-Yu; Luo, Tong; Li, Yanli; Tu, Yun-Feng; Shen, Ying-Ying; Zeng, Gui-Hua; Chen, Dong-Wan; Wang, Ye-Ran; Chen, Li-Yong; Wang, Yan-Jiang; et al. (Frontiers in Aging Neuroscience, 2022)
Background Cognitive impairment (CI) has become a worldwide health problem. The relationship between CI and uric acid (UA) is contradictory. Objective We included participants with a full spectrum of CI, from cognitively unimpaired (CU) to dementia, from the Chongqing Ageing & Dementia Study (CADS). Methods First, we identified the relationships between serum UA (sUA) and cognitive function in different stages of CI. Second, we analysed these relationships among different stages and types of CI. Finally, we explored the association between sUA and amyloid/tangle/neurodegeneration (ATN) biomarkers. Results We recruited 427 participants from the CADS, including 382 participants with mini-mental state examination (MMSE) evaluation. The levels of sUA were positively correlated with MMSE scores (p < 0.001), and the correlation was prominent in the course of dementia and in the type of Alzheimer’s disease (AD). The levels of UA had a positive correlation with plasma amyloid-β 42 (Aβ42) (p = 0.004). Higher levels of sUA weakened the correlation of MMSE scores with CSF ATN biomarkers and the correlation of CSF Aβ42 with tau. Conclusions UA is positively correlated with cognitive function, especially in the advanced stage of AD. The probable neuroprotective effects of sUA mainly act on Aβ42 and the downstream pathological cascade.